Potential competitiveness of Saint Petersburg's industries - Grigori Dudarev (The Research Institute of the Finnish Economy (ETLA), 2000)
This study is a sub-report of the ongoing larger project called “Long-term Industrial Development Strategies for Saint Petersburg”. The aim is to anticipate which manufacturing and service industries of Saint Petersburg will have a competitive edge in Russian and later in international markets. Simultaneously we will develop suitable industrial strategies, which will support this development. Here we have presented a preliminary theoretical approach, which we will develop further as the project advances. By using Porter's diamond model we will describe the competitiveness of the most outstanding industries of Saint Petersburg. Porters cluster model is used as a tool to make projections of possible future cluster development. We have taken into account also the business environment of a transition economy and the effect of foreign direct investment. In Russia, both local and central government can have a remarkable positive or negative impact on the development of enterprises and entrepreneurship. In this preliminary study we will present the industries of Saint Petersburg by using rather extensive data. There is large industrial capacity for producing power technology, heavy machinery and related metallurgy. Booming industries are the foodstuff industry and information technology, especially programming. Saint Petersburg is a transport junction of Northwest Russia, which offers excellent business possibilities. Huge unutilised potential is in tourism. – Russia ; Saint Petersburg ; Industries ; Competitiveness – – Selvitys on osa laajempaa tutkimusprojektia “Pietarin pitkän ajan elinkeinopoliittiset kehittämisstrategiat”. Hankkeessa on tavoitteena selvittää mitkä Pietarin teollisuuden ja palvelujen toimialat pitkällä ajalla voisivat kehittyä Venäjän sisällä kansallisesti ja myöhemmin kansainvälisesti kilpailukykyisiksi. Samalla hahmotellaan tätä kehitystä tukevaa elinkeinopoliittista strategiaa. Tässä työssä on esitetty alustava teoreettinen viitekehikko, jota kehitetään projektin kuluessa. Porterin kilpailukykymallin puitteissa kuvataan Pietarin merkittävien toimialojen kilpailukykyä. Tulevaa kehitystä visioidaan klusterimallin avulla. Merkittävästi kilpailukykyyn vaikuttaa siirtymätalouden puitteet ja ulkomaiset investoinnit. Myös julkinen valta, Venäjän keskusvalta ja Pietarin omat päätöksentekijät voivat ratkaisevasti edistää tai huonossa tapauksessa hidastaa elinkeinoelämän kehitystä. Esitutkimuksessa esitellään Pietarin elinkeinoelämä runsaan data-aineiston avulla. Kaupungissa on merkittävä teollinen kapasiteetti energiateknologian valmistuksessa sekä raskaassa koneenrakennuksessa ja metallurgiassa sekä laivanrakennuksessa. Tällä hetkellä nopeimmin kasvaa kuitenkin elintarviketeollisuus ja informaatioteknologia, lähinnä ohjelmistojen tuotanto. Pietari on Luoteis-Venäjän kuljetusten solmukohta, mikä tarjoaa pohjan erilaisille liiketoiminnoille. Turismissa on huomattavasti hyödyntämättömiä mahdollisuuksia. – Venäjä ; Pietari ; toimialat ; kilpailukyky
Keywords: 330